Application of Nurses' Clinical Authority at Hospital X Jakarta: A Study of the Implementation of Clinical Assignment Letters - Lumban Tobing, Masri Desy Suzanna; Tarigan, Emiliana; Kusumaningsih, Indriati (Perkumpulan Alumni dan Santri Mahyajatul Qurro', 2024)
Clinical nurses ought to exercise their clinical authority in accordance with the provisions outlined in the Clinical Assignment Letter and Details of Clinical Authority, as well as complete the credentialing process. However, this implementation has not been fully utilized or communicated to staff at Hospital. The aim of this research is to identify the mechanism for implementing clinical authority for PK I-III nurses upon receiving SPK in the inpatient room at Hospital X Jakarta. The research design utilizes the qualitative approach of hermeneutic phenomenology, and data collection is carried out through in-depth interviews. A total of 17 participants are involved, including 14 clinical nurses (PK I: 6, PK II: 6, PK III: 2), as well as 3 managerial nurses (2 heads of inpatient units and 1 inpatient coordinator). The thematic data analysis follows the Colaizzi method, and 3 themes emerge from the research findings: the application of clinical authority for PK I-III nurses, the availability of management elements in the application of clinical authority for PK I-III, and the lack of optimal management functions in the application of PK. The application of clinical authority in this research encompasses independent and collaborative actions, and it is essential to strengthen regulations, resocialize, and implement an electronic system to facilitate processes. To ensure that nurses work according to their qualification level, hospitals should reinforce regulations and supervision, provide support and commitment, and resocialize SPO, SPK, and RKK.